Transcriptomics analysis reveals potential mechanisms underlying mitochondrial dysfunction and T cell exhaustion in astronauts’ blood cells in space - Moreno-Villanueva, Maria; Jimenez-Chavez, Luis E.; Krieger, Stephanie; Ding, Liang-Hao; Zhang, Ye; Babiak-Vazquez, Adriana; Berres, Mark; Splinter, Sandra; Pauken, Kristen E.; Schaefer, Brian C.; Crucian, Brian E.; Wu, Honglu (Frontiers in Immunology, 2025)
IntroductionThe impact of spaceflight on the immune system and mitochondria has been investigated for decades. However, the molecular mechanisms underlying spaceflight-induced immune dysregulations are still unclear.MethodsIn this study, blood from eleven crewmembers was collected before and during International Space Station (ISS) missions. Transcriptomic analysis was performed in isolated peripheral blood mononuclear cells (PBMCs) using RNA-sequencing. Differentially expresses genes (DEG) in space were determined by comparing of the inflight to the preflight samples. Pathways and statistical analyses of these DEG were performed using the Ingenuity Pathway Analysis (IPA) tool.ResultsIn comparison to pre-flight, a total of 2030 genes were differentially expressed in PBMC collected between 135 and 210 days in orbit, which included a significant number of surface receptors. The dysregulated genes and pathways were mostly involved in energy and oxygen metabolism, immune responses, cell adhesion/migration and cell death/survival.DiscussionBased on the DEG and the associated pathways and functions, we propose that mitochondria dysfunction was caused by constant modulation of mechano-sensing receptors in microgravity, which triggered a signaling cascade that led to calcium overloading in mitochondria. The response of PBMC in space shares T-cell exhaustion features, likely initiated by microgravity than by infection. Consequences of mitochondria dysfunction include immune dysregulation and prolonged cell survival which potentially explains the reported findings of inhibition of T cell activation and telomere lengthening in astronauts.ConclusionOur study potentially identifies the upstream cause of mitochondria dysfunction and the downstream consequences in immune cells.